Peer‐driven family support services in the context of first‐episode psychosis: Participant perceptions from a Canadian early intervention programme. Issue 2 (11th December 2018) - Levasseur, Mary A.; Ferrari, Manuela; McIlwaine, Sarah; Iyer, Srividya N.
Abstract : Aim: This paper aims to advance our understanding of the experience of participating in peer support groups for family members of persons with psychosis and to expand the scant body of literature on peer support in the context of early intervention services for psychosis. Such an examination is relevant because the implementation and uptake of family‐focused interventions remain inconsistent in early intervention services, despite their proven benefits. Methods: To enable family caregivers to support one another, a family peer support project was initiated at an early intervention service for psychosis in Montreal, Canada. A family peer support provider and researchers collaboratively designed and conducted this study to examine the experience of those who participated in family peer support groups. Forty‐four family members completed an English or French online questionnaire. Thematic analysis was used to code responses to open‐ended questions to unpack crucial elements of this peer support intervention. Results: Three key themes were identified—the impact of psychosis on families; understanding and coping with psychosis through family peer support; and improving family peer support services. Mutual support through sharing experiences; gains in knowledge of the illness and its treatment; emotional support; and increased caregiving and self‐care capacities and skills were identified as critical benefits of family peer support. Conclusion: Family peer support can be an acceptable and cherished means of engaging and sustaining families and enhancing their caregiving skills. Its integration into early intervention services holds the promise of helping promote recovery and reducing caregiver burden.